2018
DOI: 10.31128/ajgp-03-18-4539
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of late-preterm infants: A pragmatic review

Abstract: This article is the fifth in a series on paediatric health. Articles in this series aim to provide information about diagnosis and management of presentations in infants, toddlers and pre-schoolers in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Similarly, a study examining infants born without severe brain lesions between 2013 and 2015 reported that language developmental delay had the highest incidence (20.7%), and severe language developmental delay also had a high incidence (4.2%) 18) . Prior studies have reported that infants with a clear language developmental delay without neurological deficits continue to show language developmental delay until they reach school age 19) 11,[20][21][22][23][24] . In our study, prenatal steroid use contributed to normal development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study examining infants born without severe brain lesions between 2013 and 2015 reported that language developmental delay had the highest incidence (20.7%), and severe language developmental delay also had a high incidence (4.2%) 18) . Prior studies have reported that infants with a clear language developmental delay without neurological deficits continue to show language developmental delay until they reach school age 19) 11,[20][21][22][23][24] . In our study, prenatal steroid use contributed to normal development.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis among MLPT is better compared to the very preterm, the risk of developmental impairment among MLPT, compared to their term counterparts is two-three times higher 8 , 10 – 12 . During the last few months of pregnancy, the fetal brain increases rapidly in size and in complexity through intense neuronal branching, synaptogenesis and the beginning of myelination 13 , 14 .…”
Section: Introductionmentioning
confidence: 91%
“…Developmental challenges span a spectrum of domains such as cognitive, motor, behavioural, vision, hearing, sleep and language skills [5][6][7][8][9] . The severity of developmental impairment is more pronounced with decreasing gestational age, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of preterm infants has significantly decreased recent years along with the advances of neonatal healthcare and medical treatments (Swamy et al, 2008; Glass et al, 2015; Bell et al, 2022), whereas preterm infants are still at high risk of neurodevelopmental deficiency in early life as well as late childhood mortality, and late onset mental and behavioral disorders (Vohr, 2013; Patel, 2016; Zhao et al, 2022). How to prevent the neurodevelopmental deficiencies in these infants has been put in the center of child healthcare (Srinivas Jois, 2018). Current interventional strategies in promoting neurodevelopment among preterm infants are still lacking and less than optimal due to the underlying mechanisms of neurobehavioral development understudied in these high-risk population, which hindered the timely prevention, treatment, and prediction of neurobehavioral deficiencies in the early life stages.…”
Section: Introductionmentioning
confidence: 99%
“…deficiencies in these infants has been put in the center of child healthcare (Srinivas Jois, 2018). Current interventional strategies in promoting neurodevelopment among preterm infants are still lacking and less than optimal due to the underlying mechanisms of neurobehavioral development understudied in these high-risk population, which hindered the timely prevention, treatment, and prediction of neurobehavioral deficiencies in the early life stages.…”
mentioning
confidence: 99%